We have the next equation
![2x-10y=-10](https://img.qammunity.org/2023/formulas/mathematics/college/vrl8lk34ido9mvl66is4hbysl54isxoj02.png)
the y- intercept is where x=0
so we need to substitute the value of x=0 and find the value of y
![\begin{gathered} 2(0)-10y=-10 \\ -10y=-10 \\ y=(-10)/(-10)=1 \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fi04xads7oz3guvjt1mlqg0xgbcsoq87z2.png)
the y-intercept is (0,1)
the x-intercept is where y=0
so wee need to substitute the value of y=0 and find the value of x
![\begin{gathered} 2x-10(0)=-10 \\ 2x=-10 \\ x=(-10)/(2) \\ x=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/irk1v371ch3i02g00ryw5isw37ugzyw6y2.png)
the x-intercept is (-5,0)